2017
DOI: 10.1109/led.2017.2721381
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Limit of Nanoscale Phototransistors

Abstract: In this paper the optical gain mechanism in phototransistor detectors (PTDs) is explored in low light conditions. An analytical formula is derived for the physical limit on the minimum number of detectable photons for the PTD. This formulation shows that the sensitivity of the PTD, regardless of its material composition, is related to the square root of the normalized total capacitance at the base layer. Since the base total capacitance is directly proportional to the size of the PTD, the formulation shows the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The measured I D is the external dark current, which can be obtained by multiplying the internal dark current by the optical gain. 29,30 Therefore, the increased optical gain caused by the passivation results in the increased I D . The optical gain of HPTs is defined as G opt ¼ hDI c /qP in , where h is the energy of an incident photon and DI c is the difference between collector photocurrent (I P ) and I D .…”
Section: Resultsmentioning
confidence: 99%
“…The measured I D is the external dark current, which can be obtained by multiplying the internal dark current by the optical gain. 29,30 Therefore, the increased optical gain caused by the passivation results in the increased I D . The optical gain of HPTs is defined as G opt ¼ hDI c /qP in , where h is the energy of an incident photon and DI c is the difference between collector photocurrent (I P ) and I D .…”
Section: Resultsmentioning
confidence: 99%
“…In its typical low-voltage operating conditions, the amplification mechanism of EI detectors is based on transistor action: namely the modulation of a potential barrier by trapped photo-generated excess carriers [37,38]. However, it has been observed that when the EI detectors are biased to higher voltage, a high enough field is created at the heterojunction to trigger Geiger-like operation [39,40].…”
Section: Programmable Operating Modes For An Electron-injection Sensormentioning
confidence: 99%
“…Electrical functionalization of Al 2 O 3 via reliable and spatially-accurate control of its conductivity could enable novel sensing technologies encompassing electrical contacts embedded in a mechanically hard, chemically inert, and electrically insulating dielectric matrix. Examples of such technological applications include photon emission and detection 7,[16][17][18][19] , low-energy in-terconnects [20][21][22] , energy conversion 1,23,24 , and implantable devices [25][26][27] . We here present an effective method for the non-subtractive nanopatterning of electrically conductive wires and other features embedded in a dielectric Al 2 O 3 substrate, using focused ion beam (FIB).…”
Section: Thin Films | Alumina | Dielectrics | Defect Engineering | Co...mentioning
confidence: 99%